If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3b+12-5b=22
We simplify the equation to the form, which is simple to understand
3b+12-5b=22
We move all terms containing b to the left and all other terms to the right.
+3b-5b=+22-12
We simplify left and right side of the equation.
-2b=+10
We divide both sides of the equation by -2 to get b.
b=-5
| 0.07-0.06(5x+4)=0.06x+0.13 | | 4x+13=-7x-30 | | 4x^2-26-14= | | 32m+54m+22=0 | | 6x-4x+20=-16 | | 2+3v=-6v-16 | | 3x+20+2(4x+4)=2x | | 26-(4x-11)=5(x+7) | | -(5z+1)=18 | | 4x+8-3x=14 | | 6x^3=5x^2 | | 3x+5.2=2-5y | | x+5=x+0 | | -13+7=-h-7+7 | | 3x-15=17-x | | 3(5y+2)-y=(2y-3) | | x=23-(-11) | | 8-3x=3x+2 | | 66=9x-13-8x+29 | | x/8+6=-12 | | 23-(-11)= | | w+(-9)=-4 | | 3x-15=3x | | 8x=6x-14 | | 2x-3=32 | | 15=5x-3(x+7) | | 4x-6=10x | | 21+29x=42+22x | | 81k^2-49=0 | | -[4z-(12z+6)]=6+(7z+7) | | 8-2a=-12 | | 11=7(x-3)+21 |